2017
DOI: 10.1016/j.conbuildmat.2017.08.147
|View full text |Cite
|
Sign up to set email alerts
|

Advanced analytical techniques in fatigue and rutting related characterisations of modified bitumen: Literature review

Abstract: Abstract:Fatigue and rutting are the two major failure distresses in flexible pavement that affect significantly the serviceability of pavement. The properties of bitumen have a direct effect on controlling the fatigue and rutting distresses. Because of the increase in vehicular loading and repetitions, the modification of neat bitumens becomes a widespread practice to improve their 2 mechanical properties. Any improvements obtained from developing modified binders need be reflected by fundamental testing para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…According to AASHTO M-332 51 Accumulated (total) strain with respect to time was calculated using a semi-empirical equation 46,52 and based on phase angle (δ) and shear complex modulus (G*). Figure 13 and Figure 14 show that the accumulated strain was influenced by the percentage of the molasses used.…”
Section: Multiple Stress Creep Recovery (Mscr) Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to AASHTO M-332 51 Accumulated (total) strain with respect to time was calculated using a semi-empirical equation 46,52 and based on phase angle (δ) and shear complex modulus (G*). Figure 13 and Figure 14 show that the accumulated strain was influenced by the percentage of the molasses used.…”
Section: Multiple Stress Creep Recovery (Mscr) Test Resultsmentioning
confidence: 99%
“…Bohlin Dynamic Shear Rheometer (DSR) instrument was used to perform MSCR test for RTFOconditioned BB and MMB's in accordance with AASHTO T-350 standard procedure 45 . The test was used to evaluate the non-recoverable creep compliance (Jnr), which is the measure of the binder's potential for a permanent deformation (rutting) under cyclic loading 46,47 . During the test, the applied stress level started witha 0.1 kPa and, after 10 creep/recover cycles, the stress level was increased to 3.2 kPa.…”
Section: Multiple Stress Creep Recovery (Mscr) Testmentioning
confidence: 99%
“…Additionally, several studies indicated that WMA additives could alter bitumen basic and rheological properties to different extents [11][12][13][14]. This means that traditional bitumen characterisation methods such as penetration or viscosity, or the Superpave performance indicators, such as rutting (G*/sind) or fatigue cracking (G*sind) parameters, may not be valid in characterising the behavior of WMA modified binders since these methods are intrinsically developed for unmodified bitumen [15][16][17]. Bahia et al [18] reported that the Superpave rutting and fatigue cracking parameters had a weak correlation with the performance of asphalt mixtures manufactured with modified binders.…”
Section: Introductionmentioning
confidence: 99%
“…Utilising the Dynamic Shear Rheometer (DSR), the time sweep repeated cyclic loading test allows for the fatigue characteristics to be measured, simulated and monitored directly through the damage behaviour of binders. This method defines the fatigue properties of binders and can be correlated with asphalt mixtures and long-term, field pavement performance [20,21]. Different approaches have been applied to evaluate the fatigue binder damage properties including the dissipated energy approach, which can provide a fundamental fatigue law for bituminous materials [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%